Dissociable Neural Systems Support Retrieval of How and Why Action Knowledge. - Spunt, Robert P.; Falk, Emily B.; Lieberman, Matthew D. (Psychological Science., 2010)
A study examined the neural bases of retrieving “how” and “why” knowledge for linguistic action stimuli. Data were obtained from 16 right-handed, English-speaking participants who undertook an ecologically valid free-recall task. Findings revealed support for the proposition that there is more to action than acting, and that actions indicate both movements of the body and belief-desire states of the mind. Findings suggested that to the extent that individuals represent one or the other, dissociable neural systems play a role. Findings are discussed in detail.